Effect of dry-land drill on the performance of female athletes in artistic swimming - Ntomali, S.; Chairopoulou, C.; Venetsanou, F.; Kyprianou, M.; Psychountaki, M. (Facta Universitatis: Series Physical Education and Sport, 2021)
It is a common practice among female athletes of artistic swimming to execute a dry-land drill of their routine just before its final execution in the water. The potential advantages of this established procedure have never been confirmed on an experimental basis. This study aimed at providing statistical evidence vindicating the dry-land drill. Forty seven Greek athletes of artistic swimming (seven of whom belong to the Greek National team) were given a routine containing standard figures, positions and movements. This routine was performed twice, with and without prior dry-land drill, executed in a random order with a lapse of one week between the two performances. The same three international judges were recruited to rate the performances in the standard three panels of execution, difficulty and artistic impression. The ratings of the performance including a dry-land drill were significantly better (paired t-test, p<0.001) than those without it. This improvement was consistent in all categories and levels of athletes. The enhancement in the performance brought about by the execution of a dry-land drill was more pronounced in younger athletes. The improvement in athletes` performance when they execute a dry-land drill may play an important role in the ranking of the athletes in national and international events. Dry-land drill should be recommended as a standard operating procedure in artistic swimming.